6(-7+9y)=

Simple and best practice solution for 6(-7+9y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(-7+9y)= equation:


Simplifying
6(-7 + 9y) = 0
(-7 * 6 + 9y * 6) = 0
(-42 + 54y) = 0

Solving
-42 + 54y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '42' to each side of the equation.
-42 + 42 + 54y = 0 + 42

Combine like terms: -42 + 42 = 0
0 + 54y = 0 + 42
54y = 0 + 42

Combine like terms: 0 + 42 = 42
54y = 42

Divide each side by '54'.
y = 0.7777777778

Simplifying
y = 0.7777777778

See similar equations:

| 14k+25=4k+95 | | 15/16x-11/19y=-3 | | (5x^6+8y^2)(5x^6+8y^2)= | | 2x+3=4cx+5 | | 5(3x+1)=7(5x+7)+2 | | 89j+4=23j+70 | | 4/3(3.14/1)(5832/1)= | | -8-4(2+8k)= | | 10(y-1)=-2(6+y) | | 3.14(36)(18)= | | -9(-2-8g)= | | -40=-5Y | | 2x^2+19x=32 | | 5x+7-4x=-21 | | 5x-24+3x+36=35+6x-2 | | 2x+5y=17-4x | | 18=v+20 | | 9c+10=100 | | U/3-7=-2 | | N+(n+2)+(n+4)=171 | | 6m^2+7x=5 | | 7X-4X+3=2X-8 | | 7(9b+6)= | | y+4x=14 | | (3-2x)=14 | | 6x-16=16-2x | | 5x+2(x-6)=4(x+1)-3 | | 2x+4=10+5 | | 9n=536 | | 7=2+t | | 8x+40=90 | | -9(6f-3)= |

Equations solver categories